Knowledge of health in Peru - 17th century - Zarate-Cárdenas, Esteban Eduardo (2017)
During the Viceroyalty of Peru, hospitals and universities were developed by Christian charity. Rote learning process, ecclesiastical hegemony, and poor organization frustrated innovative ideas about sciences by absence of a civilian elite capable of formulating higher education policies. The arrival of the Royal Philanthropic Expedition of the Vaccine, in 1806, spread the knowledge and the basis of sanitary organization. The Departmental Vaccination Boards were established, whose management occurred within contradictions in the first public policies of sanitary control. This situation remained until the Anatomical Amphitheater was founded.